CP-015 Potentially harmful excipients in medicines for hospitalised neonates. (25th February 2017) - Sviestina, I; Mozgis, D
Abstract : Background: Medicines used in neonates contain different excipients, which may not be safe in this age group. Purpose: To analyse the frequency that hospitalised neonates are exposed to potentially harmful excipients (HE) and to identify possible substitutes for medicines containing HE. Material and methods: This was a retrospective observational study at a university paediatric hospital. All hospitalised neonates were included. Neonates were divided into four groups according to gestational age (<28 weeks; 28 to <32 weeks; 32 to <37 weeks; and >37 weeks). The study period was from 1 September 2015 to 29 February 2016. All medicines and food supplements, except blood products, glucose and electrolyte solutions, vaccines, parenteral nutrition products and contrast agents, were analysed. The following excipients were analysed: parabens, polysorbate 80, propylene glycol, benzoates, saccharin sodium, sorbitol, ethanol and benzalkonium chloride. Excipients were identified from the Summaries of Product Characteristics. Substitutions were analysed according to Nellis et al ( Paediatr Drugs 2016, Product substitution study). Results: 327 neonates were hospitalised during the study period. Of these, 296 (102 (35%) preterm) included in the study received 1472 prescriptions for 106 medicines. The most often used formulations were intravenous (48/106; 45%), oral solid formulations (20; 19%) and topical formulations (16; 15%). The total number of different excipients was 169. In total, 29/106 (27%) medicines contained at least one HE. 82/102 (80%) preterm and 118/194 (61%) term neonates received medications with at least one HE. Substitution was possible for 9/29 (31%) HE containing medicines. Therefore, the clinical pharmacist prepared leaflets and recommendations in the hospital intranet warning doctors about currently used medicines with HE. There was also information about the HE that these products contain and the possible adverse reactions. Conclusion: Usage of HE can be reduced by using HE-free products available on the European market. However, substitution was possible in only a small number of cases. Therefore, the main focus should be on information and education of hospital specialists on which HE are present in medicines, what adverse reactions they may cause and how to avoid usage of these medicines. No conflict of interest